Enhanced electrocatalytic oxygen reduction reaction from organic-inorganic heterostructure. (1st February 2022) - Samanta, Madhupriya; Ghosh, Shrabani; Mukherjee, Moumita; Das, Biswajit; Bose, Chayanika; Chattopadhyay, Kalyan K.
Abstract: Herein, molybdenum disulfide nanoflakes decorated copper phthalocyanine microrods (CuPc-MoS2 ) are synthesized via two step simple hydrothermal method. The as synthesized hybrid along with pure molybdenum disulfide (MoS2 ) nanoflower and pure copper phthalocyanine (CuPc) microrods are well characterized by various techniques that confirm phase, morphology, elemental compositions etc. Next, electrocatalytic oxygen reduction reaction towards fuel cell is investigated in alkaline medium and obtained results proclaim that our CuPc-MoS2 heterostructure outperforms the other two constituent materials. Efficient oxygen reduction is achieved following four electron pathway by CuPc-MoS2 whereas partial reduction is done through two electron process by CuPc and MoS2 separately. Long-time durability test reveals almost 97.6% retention after 8000s that eventually dictate us that CuPc-MoS2 heterostructure can be the efficient cathode electrocatalyst for future generation fuel cell. Graphical abstract: Image 1 Highlights: Hierarchical growth of MoS2 on CuPc rod is formed using low temperature facile route. Enhanced electrocatalytic ORR of CuPc-MoS2 is observed than bare counterparts. Long-time durability test reveals almost 97.6% retention after 8000s for CuPc-MoS2 . Structure activity relationship and active edge sites play role for enhanced ORR.